Effects of Atmospheric Circulation on Stream Chemistry in Forested Watersheds Across the Northeastern United States: Part 1. Synoptic‐Scale Forcing. Issue 13 (28th June 2021) - Siegert, C. M.; Suriano, Z. J.; Leathers, D. J.; Gold, A. J.; Addy, K.; Schroth, A. W.; Seybold, E.; Inamdar, S.; Levia, D. F.
Abstract: Synoptic typing is a method of classifying atmospheric conditions (i.e., pressure, temperature, wind direction) and can be used to relate those conditions to terrestrial processes. In this study, a daily synoptic calendar was developed for the northeastern United States to assess the atmospheric controls on variations in stream chemistry across three forested watersheds in Vermont, Rhode Island, and Maryland. Stream discharge along with dissolved organic carbon and nitrate concentrations were monitored in situ from March to November for 3 years (2014–2016) and then compared to the regional daily synoptic calendar to assess (a) which atmospheric patterns exported the greatest flux of water and solutes, (b) whether all three watersheds responded similarly to the regional atmospheric patterns, and (c) how these fluxes changed seasonally. Seven broad categories of atmospheric patterns were identified. In general, low pressure systems situated over the Great Lakes region produced the most rainfall which resulted in the highest peak streamflow by event along with daily fluxes of DOC and NO 3 − ‐N across the watersheds. In contrast, southwest flow regimes and Northwest Flow regimes occurred the most frequently (36% and 14% of study days, respectively) and resulted in the largest overall export (+50% of total) of water and solutes from the three watersheds. Regardless of watershed size or location, streamflow dynamics were similar when classified using synoptic typing. As such, valuable insight into the meteorological mechanisms behind temporal variation in carbon and nitrate stream export in forested watersheds can be gained by employing regional synoptic weather analyses. Key Points: Synoptic‐scale weather patterns are associated with terrestrial stream dynamics at the regional scale Regardless of watershed size or location within the study region, water and solute fluxes were similarly classified using synoptic typing Storms from more frequent synoptic types dominated water and solute fluxes compared to storms from larger, infrequent synoptic types